Post-Pandemic Risk Assessment and Safety Management at Academic Institution Environment - Frestiqauli, Santi; Nandalianadhira, Nafisa; Hermanto, Mochammad Fathurridho; Samuel, Samuel (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2023)
The World Health Organization (WHO), on March 11, 2020, declared the novel coronavirus (COVID-19) outbreak a global pandemic. Safety, people protection, equipment and environmental protection are serious concerns anywhere, including in an institution or university environment. In the meantime, the number of accidents has increased in academic institutions nationwide. Students, staff, lecturers, and academic personnel are involved in activities that expose them to minor to major fatal accidents. This study developed risk assessment using combinations of hazards and risk factors to scale measures in a risk reduction action plan. Health, safety and environment risk assessment conducted for 27 assessed hazardous activities at 18 locations divided into three areas: laboratories, public facilities, and offices at the Department Ocean Engineering Sepuluh Nopember Institute of Technology. The frequency and severity of health hazards were higher in accumulation number, which is 790, compared to safety hazards, which score 509, and environmental hazards, with 104. The highest number for accumulation of potential hazards in health, safety, and environment for laboratories area is 883, followed by accumulation of potential hazard at health, safety, and environment for office area and public facilities area with scores 239 and 281.